METHODOLOGY OF FORMATION OF STRATEGY FOR DEVELOPMENT OF MACHINE BUILDING ENTERPRISES ON THE BASIS OF VALUE COMPETENCIES IN THE CONDITIONS OF GLOBALIZATION - PLYASKINA, ALONA; YAKYMCHUK, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
It is established that an effective development strategy contributes to the rapid adaptation of enterprises to changes in the environment and conditions of globalization, and vice versa, the development of globalization processes allows to maintain a competitive level of entrepreneurship. The result of the work should be a focused strategy of the enterprise, ie the concept is developed and defined by it a system of measures aimed at achieving competitive advantage. Therefore, the development of an effective competitive strategy for all enterprises is an important necessity and has undeniable practical value. However, it is important to note the difficulty of choosing the optimal competitive strategy from a variety of strategies, provided that all important aspects are taken into account. The next step of the study should be to develop a model of effective choice of competitive strategy, which takes into account a number of factors, allows for critical quantitative and qualitative analysis of strategic alternatives and involves the use of optimal tools. This will form a truly competitive strategy of the enterprise and ensure its successful practical implementation. Speaking about the choice and feasibility of a competitive strategy, it is important to mention the value chain of the company's product. The main goal of each enterprise is not just its survival in the market, but stable operation and constant economic growth. To achieve this goal, it is necessary to develop an effective development strategy on the basis of which to create and implement competitive advantages. All this will give the company the opportunity to answer vital questions: where to operate (in what industry or in which markets), how to allocate resources, how to compete effectively with other companies, how to develop stably in the future.
Keywords: enterprise; enterprise development; methodology; value competencies; globalization